KOMODIFIKASI PEREMPUAN PADA AKUN INSTAGRAM @UNSYIAH.CANTIK - Salwa Alifa (Jurnal Riset Komunikasi, 2023)
Women and beauty are aspects that have a role in shaping the construction according to the role in the social environment. The role of the physical has always been the dominant discussion in the local and global scope. Instagram plays an active role as a center for managing thoughts and forming constructions among the community. The Instagram account @ unsyiah.cantik as a product of digitization is seen as an account that commodifies women as objects. The purpose of this research is to identify the commodification process that occurs on the Instagram account @ unsyiah.cantik. Qualitative research using cyber media analysis techniques. The commodification that occurs on the Instagram account @ unsyiah.cantik is the commodification of content and audiences. This is related to uploading photos of beautiful female students in order to get lots of followers and likes to get material benefits. The Instagram account @ unsyiah.cantik also adheres to the male gaze view which depicts a dominant male-centered viewpoint in visual representation, especially in the context of Instagram media photos.